Gastroparesis syndromes: Response to electrical stimulation. Issue 3 (31st January 2019) - Abell, Thomas L.; Kedar, Archana; Stocker, Abigail; Beatty, Karen; McElmurray, Lindsay; Hughes, Michael; Rashed, Hani; Kennedy, William; Wendelschafer‐Crabb, Gwen; Yang, Xiu; Fraig, Mostafa; Omer, Endashaw; et al.
Abstract: Background and Aims: Factors underlying gastroparesis are not well defined, nor is the mechanism of action of gastric electrical stimulation (GES). We hypothesized that GES acts via several mechanisms related to underlying disordered pathophysiology. Methods: We studied 43 consecutive eligible patients with gastroparetic symptoms, previously evaluated by two methods in each of five core areas: inflammatory, autonomic, enteric, electrophysiologic, and hormonal; and also categorized by GI symptoms, metabolic status, illness quantification, and gastric physiology. We then studied 41 patients who underwent temporary GES for 5‐7 days. Thirty‐six of those patients were implanted and 30 were followed up at 6 months after permanent GES. Results: In previous but separately reported work, patients had similar GI symptoms regardless of baseline gastric emptying or diabetic/idiopathic status and all patients demonstrated abnormalities in each of the five areas studied. After GES, patients showed early and late effects of electrical stimulation with changes noted in multiple areas, categorized by improvement status. Conclusion: Patients with symptoms of gastroparesis have multiple abnormalities, including systemic inflammation and disordered hormonal status. GES affects many of these abnormalities. We conclude electrical stimulation improves symptoms and physiology with (a) an early and sustained anti‐emetic effect; (b) an early and durable gastric prokinetic effect in delayed emptying patients; (c) an early anti‐arrhythmic effect that continues over time; (d) a late autonomic effect; (e) a late hormonal effect; (f) an early anti‐inflammatory effect that persists; and (g) an early and sustained improvement in health‐related quality of life. This study is registered with Clinicaltrials.gov under study # NCT03178370 (https://clinicaltrials.gov/ct2/show/NCT03178370 ). Abstract : A consensus does not exist on the pathophysiologic factors underlying gastroparetic symptoms. Gastric electrical stimulation (GES) has early and late effects on disordered physiology in gastroparetic symptom patients. Gastric electrical stimulation might better be classified as neuromodulation due to its several possible mechanisms of action.